2019
DOI: 10.1080/2090598x.2019.1590516
|View full text |Cite
|
Sign up to set email alerts
|

Trends in surgical and ablative treatment of localised renal cell carcinoma: A review of publication trends over 16 years (2000–2015)

Abstract: Objective: To investigate the bibliometric (publication) trends in surgical and ablative treatment of localised renal cell carcinoma (RCC) over a period of 16-years, from 2000 to 2015, as publication trends reflect clinical practice and new innovations. Material and methods: We performed a systematic review using PubMed over a 16-year period from 2000 to 2015 for all published papers on surgical and ablative management of renal tumours. Data were further analysed in two time periods, period-1 (2000-2007) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Renal cell carcinomas (RCC) is the most frequent type of cancer originating from the kidney parenchyma ( Inamura, 2017 ; Pietropaolo et al, 2019 ). Every year, approximately more than 200,000 individuals are newly diagnosed with RCC worldwide ( Bray et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinomas (RCC) is the most frequent type of cancer originating from the kidney parenchyma ( Inamura, 2017 ; Pietropaolo et al, 2019 ). Every year, approximately more than 200,000 individuals are newly diagnosed with RCC worldwide ( Bray et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the widespread application of radiological imaging (e.g., ultrasonography and computerized tomography), the cases of RCC could be more frequently detected. 2 Although there are various types of therapies for RCC of different stages, surgery is the only effective treatment for localized RCC. 3 Thus, radical nephrectomy (RN) and partial nephrectomy (PN) were established successively.…”
Section: Introductionmentioning
confidence: 99%
“…popularity due to its favorable oncologic efficacy and complication profile. When comparing papers on PubMed from 2000 to 2007 versus 2008 to 2015 using systematic review per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, Pietropaolo et al reported a change of +109% (P = 0.002) and +78% (P = 0.036) was seen for cryoablation (CA) and radiofrequency ablation (RFA), respectively [2]. Shi et al reported an increase in TA from 8.1% in 2004 to 14.9% in 2016 using the retrospective Surveillance, Epidemiology, and End Results (SEER)-Medicare associated databases [3].…”
Section: Introductionmentioning
confidence: 99%